Discovery of 3-(benzofuran-2-ylmethyl)-1H-indole derivatives as potential autophagy inducers in cervical cancer cells - Siddiqui, Shaziyaparveen K.; SahayaSheela, Vinodh J.; Kolluru, Srinivas; Pandian, Ganesh N.; Santhoshkumar, Thankayyan R.; Dan, Vipin M.; Ramana, V, Chepuri (Bioorganic & Medicinal Chemistry Letters, 2020)
In this manuscript we have documented the identification of a novel anticancer scaffold 3-(benzofuran-2-yl-methyl)-1H-indole. This scaffold has been designed by tweaking the known bisindolylmethane scaffold of natural products that display a wide range of biological activities. A series of 24 new conjugates have been synthesized and among them 5 derivatives exhibited IC50 values less than 40 mu M against two cervical cancer cell lines SiHa and C33a. Further mechanistic studies of two compounds 3eb and 3ec revealed that the toxicity of these compounds was due to the effective induction of autophagy mediated cell death. The autophagy induction was confirmed by the progressive conversion of LC3I to LC3II and downregulation of p62 in cervical cancer cells.
Keywords: Autophagy; Benzofuran; Bisindolylmethane; Cervical cancer; Friedel-Crafts alkylation